The polymorphisms of protein-tyrosine phosphatase receptor-type delta gene and its association with pediatric asthma in the Taiwanese population - Shyur, Shyh-Dar; Wang, Jiu-Yao; Lin, Cherry Guan-Ju; Hsiao, Ya-Hsin; Liou, Ya-Huei; Wu, Ying-Jye; Wu, Lawrence Shih-Hsin (European journal of human genetics : EJHG, 2008)
We previously reported an association between genetic differences of pediatric asthma subtypes and a short tandem repeat (STR) marker, D9S286. It has been known that the protein-tyrosine phosphatase receptor-type delta (PTPRD) gene is located downstream of D9S286 and that the physical distance between them is about 0.25 Mb. We selected and conducted genotyping on 76 single-nucleotide polymorphisms (SNPs) that encircle the genomic region of PTPRD in Taiwanese children with or without asthma. A total of 996 subjects were divided into testing group (674 subjects) and validation group (322 subjects). The results were further validated with the third subject group (611 subjects) recruited from different geographical regions. After Bonferroni correction, 3 out of 80 SNPs were found to be strongly significant ( P <0.05/76=0.000658) in the allele frequency test. This association was confirmed by validation groups. The results indicate that polymorphisms of PTPRD are strongly associated with pediatric bronchial asthma in the Taiwanese population.